Uranium isotopes as tracers of groundwater evolution in the Complexe Terminal aquifer of southern Tunisia. (10th May 2020) - Hadj Ammar, Friha; Deschamps, Pierre; Chkir, Najiba; Zouari, Kamel; Agoune, Aissa; Hamelin, Bruno
Abstract: The Complexe Terminal (CT) multi-layer aquifer is formed by Neogene/Paleogene sand deposits, Upper Senonian (Campanian-Maastrichtian limestones) and Turonian carbonates. The chemical composition and isotopes of carbon and uranium were investigated in groundwater sampled from the main hydrogeological units of the (CT) aquifer in southern Tunisia. We paid special attention to the variability of uranium contents and isotopes ratio ( 234 U/ 238 U) to provide a better understanding of the evolution of the groundwater system. Uranium concentrations range from 1.5 to 19.5 ppb, typical of oxic or mildly reducing conditions in groundwaters. The lowest concentrations are found southeast of the study area, where active recharge is supposed to take place. When looking at the isotope composition, it appears that all the samples, including those from carbonate levels, are in radioactive disequilibrium with significant 234 U excess. A clear-cut distinction is observed between Turonian and Senonian carbonate aquifers on the one hand, with 234 U/ 238 U activity ratios between 1.1 and 1.8, and the sandy aquifer on the other hand, showing higher ratios from 1.8 to 3.2. The distribution of uranium in this complex aquifer system seems to be in agreement with the lithological variability and are ultimately a function of a number of physical and chemical factors including the uranium content of the hosting geological formation, water-rock interaction and mixing between waters having different isotopic signatures. Significant relationships also appear when comparing the uranium distribution with the major ions composition. It is noticeable that uranium is better correlated with sulfate, calcium and magnesium than with other major ions as chloride or bicarbonate. The 14 C activities and δ 13 C values of DIC cover a wide range of values, from 1.1 pmc to 30.2 pmc and from −3.6‰ to −10.7‰, respectively. 14 C model ages estimated by the Fontes and Garnier model are all younger than 22 Ka and indicate that the recharge of CT groundwater occurred mainly during the end of the last Glacial and throughout the Holocene.